Restructuring Indonesia's Sub-national Public Debt: Reform or Reversion? - Lewis, Blane (2012)
Borrowing can be an efficient way for sub-national governments to acquire capital assets, but it also carries risks of fiscal distress and insolvency for borrowers. To minimise these risks, many governments around the world have developed ex-post insolvency remedies, including, most importantly, debt-restructuring mechanisms. In an effort to resurrect borrowing for local infrastructure development, the Indonesian government has designed and begun to implement debt-restructuring programs for sub-national government and sub-national government-owned water supply company defaulters. These programs constitute a major effort to reform an important, long-neglected and problematic aspect of sub-national public finances in Indonesia. There are a number of potential difficulties with the design and execution of the reforms, however, which collectively do not inspire much optimism for rapid progress in reviving financial flows to the sub-national public sector. Still, even halting advances in debt restructuring can substantially increase local infrastructure investment in the long run.